Exploring Lord Hanuman’s Communication in Tulsi’s Ramcharitmanas through The Lens of Sahridayata - Bharadwaj, Mayank; Singh, Paramveer (Bodhi: An Interdisciplinary Journal, 2024)
This article explores Lord Hanuman’s communication through the lens of Sahridayata as envisioned in Adhikary’s Sadharanikaran Model of Communication (SMC). Three incidents of Lord Hanuman has been taken in this regard. The first incident is his interaction with Lord Ram, the second with Bhagwati Sita, and the third with Vibhishan. Through these incidents, the communicative qualities of Lord Hanuman have been assessed from the perspective of Sahridayata.